Lifetime Improvement of Perovskite Solar Cell, Using a Photoactive Phase Change Material - Maryam Alidaei; V. Ahmadi; F. Arabpour Roghabadi (AUT Journal of Electrical Engineering)
Perovskite Solar Cells (PSCs) are the brilliant stars of the new generation photovoltaic technologies due to their superior features of perovskite material and high Power Conversion Efficiency (PCE) that has reached up to 25.5%. Their stability is the main challenge that should be addressed for the commercialization of PSCs. The perovskite structure is decomposed to its precursor in the face of continuous light irradiation (mainly UV light), humidity, and heat. In this paper, mesoporous PSCs with structure of FTO (400 nm)/Compact TiO2 (30 nm)/Mesoporous-TiO2 (330 nm)/CH3NH3PbI3 (270 nm)/ P3HT (30 nm)/Au (100 nm) are fabricated in an uncontrolled environment. The UV light stability of the PSC is enhanced by adding a photoactive Phase Change Material (PCM) into the perovskite. The PCM undergoes trans-to-cis isomerization under UV light irradiation. Afterwards, the cis form absorbs the heat produced in the solar cell and converts it into its trans isomer in a reversible process. By this approach, the destructive effect of UV light and heat is prohibited, leading to the enhancement of PSC durability by almost 2.4 times compared to devices without PCM. Indeed, the PCE of the device with AzB reaches 67% of the initial PCE upon 120 min of light soaking under AM 1.5, while the device without AzB only keeps 28% of its initial PCE under the same condition. It should be noted that there is no significant difference in the PCE of both solar cells.